Firms' financial and corporate governance characteristics association with earnings management practices: a meta-analysis approach - Abdul Hamid, Fatima; Eddine, Chaabane Oussama; Ayedh, Abdullah Mohamed; Echchabi, Abdelghani (University of Tuzla, 2014)
This paper aims to investigate the association between firm’s corporate governance and financial attributes (namely, board of directors’ size, board of directors’ independence, chief executive officer (CEO) duality, ownership structure, audit type, firm’s size, firm’s return and leverage) with earnings management practices. The study applies a comprehensive meta-analysis of the findings of 25 journal articles published between 2003 and 2013. The analysis permits this research to accumulate and assimilate the results of previous literature, and their generalization to a wider range of settings. The results showed that all corporate governance and financial characteristics variables have a significant association with earnings management practices